Investigating the factors which impact SPI implementation initiatives in software SMEs—A systematic map and review. Issue 7 (25th June 2019) - Sharma, Pooja; Sangal, Amrit Lal
Abstract: Context: For successful initiation of software process improvement (SPI) initiatives in software SMEs, it is vital for the practitioners to have deep understanding of various SPI inhibitors. Objective: The paper has the following objectives: investigate factors which impact SPI implementation initiatives in software SMEs, synthesize available evidence, identify gaps between existing approaches available in the literature, and to develop the taxonomy of the factors. Methods: Database search and snowballing procedure are adapted to perform the systematic mapping and review, which includes 105 primary studies published between 2002 and 2018. Also, we reviewed the empirical studies for their rigor and relevance. Results: A total of 16 inhibitors have been identified and are grouped into PMBOK knowledge areas framework. From the rigor and relevance scores, it is observed that despite the research has been conducted in an industrial context, it lacks rigor (mean = 1.79) and thus hinders the possibility of generalizing the results. This calls for more studies with thorough empirical analysis and validation using adequate statistical tests. Conclusions: The results can help the practitioners to understand the dynamics of factors, which undermine SPI implementation in software SMEs and also to assist them in the development of effective control and mitigation strategies.